2021
DOI: 10.1002/chem.202004594
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years after the Discovery of Its Nucleolytic Activity: [Cu(phen)2]2+ Shows Unattended DNA Cleavage Activity upon Fluorination

Abstract: [Cu(phen)2]2+ (phen=1,10‐phenanthroline) is the first and still one of the most efficient artificial nucleases. In general, when the phen ligand is modified, the nucleolytic activity of its CuII complex is significantly reduced. This is most likely due to higher steric bulk of such ligands and thus lower affinity to DNA. CuII complexes with phen ligands having fluorinated substituents (F, CF3, SF5, SCF3) surprisingly showed excellent DNA cleavage activity—in contrast to the unsubstituted [Cu(phen)2]2+—in the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The positive control samples utilized in this assay were prepared as follows: linear pET20b was generated using the restriction enzyme EcoRI‐HF (New England Biolabs) according to the manufacturer’s protocol. pET20b containing a single‐strand break was prepared using the artificial nuclease [Cu(phen) 2 ] 2+ as described in the literature (52). The [Cu(phen) 2 (H 2 O)](NO 3 ) 2 used for this reaction was synthesized analogously to a literature procedure (53).…”
Section: Methodsmentioning
confidence: 99%
“…The positive control samples utilized in this assay were prepared as follows: linear pET20b was generated using the restriction enzyme EcoRI‐HF (New England Biolabs) according to the manufacturer’s protocol. pET20b containing a single‐strand break was prepared using the artificial nuclease [Cu(phen) 2 ] 2+ as described in the literature (52). The [Cu(phen) 2 (H 2 O)](NO 3 ) 2 used for this reaction was synthesized analogously to a literature procedure (53).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, some 5-fluoro substituted 1,10-phenanthrolines were prepared [ 27 ] by Skraup–Debner–Miller reaction using the corresponding fluorinated derivatives of 2-nitroaniline. In [ 28 ], the synthesis of copper coordination compounds based on 5-fluoro- and 5,6-difluorophenanthrolines was reported and it was shown that such complexes have a cytotoxic effect on cancer cells, while their toxicity to healthy cells (fibroblasts) is lower. 5,6-difluorophenanthroline has been also prepared [ 29 ] by electrolysis of 1,10-phenanthroline using a triethylamine hydrofluoric acid complex (Et 3 N·6HF) as a fluorinating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Phenanthroline containing Cu(II) complex, CPT8 ( Figure 9 , top), could downregulate the expression of MMP-2 in SK-OV-3 cells [ 121 ]. [Cu(phen) 2 (CH 3 CN)] 2+ and [Cu(dmp) 2 (CH 3 CN)] 2+ ( Figure 9 , middle row), which have a similar structure to [Cu(phen) 2 ] + , were examined for its anti-cancer activities in 2D and 3D models of human osteosarcoma (MG-63), A549, MCF-7, triple-negative breast adenocarcinoma cells (MDA-MB-231), and colorectal cancer cells (HT-29, LS174T, and Caco-2) [ 80 , 122 ]. Similar to [Cu(phen) 2 ] + , the anti-cancer activity of [Cu(phen) 2 (CH 3 CN)] 2+ and [Cu(dmp) 2 (CH 3 CN)] 2+ was attributed to the ROS production by nucleolytic activity of those Cu(II) complexes [ 80 , 122 ].…”
Section: Mmp Regulators–metal Complexesmentioning
confidence: 99%